The relationship between physical activity and stress level among university office workers / Nurfarrahanis Amran ... [et al.] - Amran, Nurfarrahanis; Syed Mud Puad, Sharifah Maimunah; A. Rahman, Muhammad Wafi; Mohd Faridz Ahmad, Mohd Faridz Ahmad (Universiti Teknologi MARA, 2023)
Office workers are a subgroup of employee who perform administrative clerical work in front of computers on regular basis. This group is characterized as the population that engages in less physical activity and tend to have higher level of stress. The main objective of this study is to determine the relationship between physical activity and stress level among office workers in a university. Physical activity level was measured with International Physical Activity Questionnaire (IPAQ-SF) (7 items) and Perceived Stress Scale Questionnaire (PSS) (10 items) was the instrumentation used to measure stress level. Total of two hundred thirteen (N=213) office workers were participated in this survey. Most of the respondents report moderate physical activity (58.2 %) and moderate level of stress (70.0%). The findings of this study showed that there was no significant relationship between physical activity and stress level (p> .05). As for conclusion, physical activity and stress level were not associated and interdependent to each other. There are multiple factors that affect physical activity engagement and stress level.